Considerações sobre o mercado de créditos de carbono: propostas de contabilização - Santin, Claiton (2012)
Due to the growth of the discussions involving less harmful trade and economic practices to the environment, as well as the use of renewable energy sources, have been increasingly frequent approaches to the Kyoto Protocol and its imposed norms to major economies. Added to these factors the Accounting International Norms in the brazilian scenario, it becomes increasingly important to find ways to clarify the accounting dealings about this question, once it has been responsible for high-value financial turns, currency which need to be properly disclosed in the accounting statements of companies participating in this market. The study performs a qualitative approach, of exploratory feature, aiming a better understanding of the subject, and developed through a literature review. Thus, this study search to analyze the accounting treatment assigned to transactions involving the market of carbon credits, identifying a series of treatments, and the almost complete lack of standardization in the area